Recent advance of single atom-based photocatalysts for energy conversion and environmental purification - Niu, Yaling; Yue, Chengcai; Li, Shuqi; Che, Guangbo; Su, Nan; Dong, Hongjun; Li, Chunmei (Carbon Letters, 2023)
Developing the high-performance semiconductor photocatalytic materials is an eternal topic under the background of the current energy and environment requirements. In recent years, single-atom photocatalysts (SAPCs) have been brought a lot of attention in energy conversion and environmental purification because of their unique characteristics and properties, including the unique coordination patterns, outstanding atomic utilization, quantum confinement effects, high catalytic activity, etc. Hence, this critical review focuses on the summarized various synthetic methods and the recent important applications of SAPCs, including photocatalytic H 2 evolution (PHE) from water splitting, photocatalytic CO 2 reduction, photodegradation of organic pollutants, etc. The prospects and challenges for future research topics of SAPCs with excellent activity and stability for various photocatalytic applications are prospected at the end of this review. We sincerely expect that this critical review can promote deep-level insight into the SAPCs subject for the future significant applications in other fields.